An Examination of the Relationship Between Characteristics of Sect-Like Religiosity and Community Volunteering Among U.S. Churchgoers - Polson, Edward C. (Review of religious research, 2018)
Previous research indicates a robust relationship between religious participation and volunteering. However, religion is a multidimensional phenomenon and relatively few studies have examined the effects that different types of religiosity have on the likelihood of volunteering. In this article I extend our understanding of the link between religion and volunteering by examining the effect that several characteristics associated with sect-like religiosity have on the likelihood of community volunteering among U.S. churchgoers. My findings indicate a more nuanced relationship between volunteering and religious belonging, practice, and experience than previous studies have shown. Density of congregational friendship networks and frequency of evangelism are found to increase the likelihood of volunteering through and for religious congregations while supernatural experiences and frequency of evangelism are found to increase the likelihood of volunteering outside of the congregation. Religious strictness is found to decrease the likelihood of volunteering outside of the congregation. Implications for our understanding of the link between religion and volunteering are discussed as well as directions for future research.